2018
DOI: 10.2337/dc18-0550
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Peer Support on Acute Care Visits and Hospitalizations for Individuals With Diabetes and Depressive Symptoms: A Cluster-Randomized Controlled Trial

Abstract: Comorbid depression is associated with increased health care utilization and cost. We examined the effects of peer support on acute care (AC) and hospital utilization in individuals with diabetes with or without depressive symptoms. RESEARCH DESIGN AND METHODS This was a cluster-randomized controlled trial conducted in 2010-2012, with the clusters being practices and their surrounding communities. Adults with type 2 diabetes who wanted help with self-management were eligible to participate. Those without a doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Studies found that early detection of anxiety and depression can significantly improve the quality of life of diabetics [49]. Besides, for patients, proper yoga and exercise [50,51], increasing peer support and company can also alleviate depression, improve the quality of life of diabetics [52]. Diabetics can broaden their social contact by closely connecting with other patients and sharing their disease experience.…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that early detection of anxiety and depression can significantly improve the quality of life of diabetics [49]. Besides, for patients, proper yoga and exercise [50,51], increasing peer support and company can also alleviate depression, improve the quality of life of diabetics [52]. Diabetics can broaden their social contact by closely connecting with other patients and sharing their disease experience.…”
Section: Discussionmentioning
confidence: 99%
“…25 Based on our findings, consideration should be given to how peer support can be influential from a population management perspective, especially given evidence on the cost-effectiveness of peer support on acute care outcomes. [26][27][28][29] Although some research exists, 22,30 we do not yet fully understand the specific peer characteristics that would optimize clinical outcomes.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…In contrast to our findings, a recent study suggests peer support is effective in reducing diabetes distress among those with type 2 diabetes. 33 Furthermore, peer support was found to be effective in reducing acute care hospitalizations for PWD with depressive symptoms but not for those without depressive symptoms, 27 suggesting a protective effect.…”
Section: Psychosocial Outcomesmentioning
confidence: 99%
“…Studies found that early detection of anxiety and depression can signi cantly improve the quality of life of diabetics [47]. Besides, for patients, proper yoga and exercise [48,49], increasing peer support and company can also alleviate depression, improve the quality of life of diabetics [50]. Diabetics can broaden their social contact by closely connecting with other patients and sharing their disease experience.…”
Section: Discussionmentioning
confidence: 99%